Analysis of the Influence of Organizational Commitment on Work Discipline of Public High School Teachers - Akhmad Ramli; Mundzir Mundzir; Ghalib Suprianto; Firman Ashadi; Opan Arifudin (Journal on Education, 2024)
Commitment is a crucial quality that educators need to possess in their work environment. Organizational commitment is one of the factors that can impact the quality of work, particularly when it comes to determining the discipline of teachers' work. Therefore, in order to maintain the excellence of schools in the eyes of the community, this must be implemented correctly by teachers with support from the schools. Surveys and documentation studies were used as data gathering methods. Forty instructors received questionnaires with a linkert scale consisting of five possible answers. With the use of SPSS, the data were processed and examined using correlation analysis, coefficient of determination, and basic linear regression analysis. The statistical testing of correlation analysis tests produced a r count of 0.6. Test indicates that organizational commitment has an impact on teachers' work discipline. Moreover, organizational commitment is impacted by the coefficient of determination calculation to the tune of 40%, other factors not included in this study account for 60% of the total. Therefore, teachers' organizational commitment is sufficient to have a maximum impact on their work discipline in carrying out their duties and obligations.